THE CORRELATION BETWEEN PAST TENSE MASTERY AND STUDENTSâ TRANSLATING IN NARRATIVE TEXT SKILL AT GRADE ELEVENTH OF SMA N 3 RAMBAH HILIR. - PARMI, YESNIDA; Rahayu, Pipit; Rasyidah, Ummi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was to see whether there is a correlation between past tensemastery and studentsâ translating narrative text at grade eleventh of SMA N 3 Rambah Hilir. Thisresearch was quantitatif research in which aid to describe about an objective situation. This researchhad two variables, Variable X ( past tense mastery) and variable Y ( translating narrative text skill).Based on the analyzed of the data it can be concluded there was a low correlation between past tensemastery and studentsâ translating narrative text skill at grade Eleventh of SMA N 3 Rambah Hilir. Thecorrelation of ârxyâ product moment was 0,137.